Striking balance freedom of expression in post-Soeharto Indonesia - Suryana, A'an (2015)
Access online through this link: https://www.plarideljournal.org/article/striking-balance-freedom-of-expression-in-post-soeharto-indonesia
Keywords: Freedom of expression; Violence; Religion; Islam